Pendampingan UMKM Madu Iro dan Madu Masriana dalam Ekspansi Pasar melalui Platform E-commerce - Aini, Agustin Nur; Rizky, Vaneza; Rohana, Lailatul; Azizah, Yuzki; Aprilia, Dina; M Taufikur Romadhon; Sholichin, Riadus (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
Business digitalization is an important factor in increasing the competitiveness of MSMEs in the digital economy era. MSMEs Madu Iro and Madu Masriana face obstacles in utilizing e-commerce platforms, such as lack of digital literacy and suboptimal marketing strategies. This community service activity aims to improve the digital skills of business actors in utilizing e-commerce as a means of market expansion. The method used is the Asset-Based Community Development (ABCD) approach through asset identification, digitalization training, implementation assistance, and evaluation of program success. The results show an increase in digital skills, an increase in the number of transactions. The success of this program proves that digitalization can increase the competitiveness of MSMEs, but sustainability remains a challenge that needs further attention.